Cross-border health and productivity effects of alcohol policies - Per Johansson; Tuomas Pekkarinen; Jouko Verho (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2012)
This paper studies the cross-border health and productivity effects of alcohol taxes. We estimate the effect of a large cut in the Finnish alcohol tax on mortality, alcohol related illnesses and work absenteeism in Sweden. This tax cut led to large differences in the prices of alcoholic beverages between these two countries and to a considerable increase in cross-border shopping. The effect is identified using differences-in-differences strategy where changes in these outcomes in regions near the Finnish border are compared to changes in other parts of northern Sweden. We use register data where micro level data on deaths, hospitalisations and absenteeism is merged to population-wide micro data on demographics and labour market outcomes. Our results on the effect of the Finnish tax cut on mortality and alcohol-related hospitalisations in Sweden are very imprecise. However, we find that workplace absenteeism increased by 5% for males and by 13% for females near the Finnish border as a result of the tax cut.
Keywords: H23; H73; I18; 330; Cross-border shopping; Alcohol taxes; Health effects of alcohol; Alkoholsteuer; Steuerwirkung; Grenzgebiet; Gesundheit; Fehlzeit; Finnland; Schweden